استخدام برنامج WEPP في دراسة كميات التربة المنجرفة والجريان السطحي لمنطقة الشيخ بدر - كبيبو عيسى; الشهابي عمران; محفوض ايلين; محمد صفوان (Latakia University Journal -Biological Sciences Series, 2017)
هدفت الدراسة إلى تقدير كميات التربة المنجرفة في منطقة الدراسة باستخدام برنامج WEPP , ثم مقارنة النتائج التي تم الحصول عليها مع نتائج دراسات حقلية سابقة من خلال استخدام ثلاث مؤشرات إحصائية وهي: معامل فعالية البرنامج MEIومعامل PBIASومعامل خطأ التقدير الإجمالي, إضافة إلى تحليل العلاقة الموجودة بين القيم المقدرة والمقاسة للانجراف والجريان السطحي. سجلت فعالية البرنامج MEIقيماً جيدة جداً بالنسبة لكميات التربة المنجرفة تراوحت بين (0,98) و (0.20), بينما سجل معامل PBIASقيماً جيدة جداً (3.2-) و قيماً مرضية (44.46), وتراوحت قيم معامل خطأ التقدير الإجمالي بين (3.2) و (44.46-). أما بالنسبة لقيم الجريان السطحي فسجلت فعالية البرنامج MEIقيماً غير مرضية بشكل عام وصلت أعلاها في تجربة شاهد 8% (-98.04) أما معامل PBIASفسجل قيماً غير مرضية في تجربة قمح 8% . و سجلت قيم معامل الارتباط R2 لكميات التربة المنجرفة و الجريان السطحي (0.333,0.83) على الترتيب. The USDA- WEPP (Water Erosion Prediction Project erosion model) represents a new generation technology for estimating soil erosion and sediment delivery from hillslope profiles and small watersheds. The main purpose of this study was evaluating the WEPP model applicability and prediction accuracy for experimental plot, by using three different statistical index: Nash–Sutcliffe simulation model efficiency (MEI), Percent Bias (PBIAS) and Error in total estimate. In addition to analyse the relationship between the estimated and measured values for erosion and runoff. MEI values For soil erosion ranged between (0.98)(very good) and (0.20) (satisfactory), while PBIAS values (3.2-)(very good) and (44.46) (satisfactory), and the values ranged between (3.2) and (-44.46) for Error in total estimate. Furthermore, runoff values were unsatisfactory in general and reached the highest point at blank 8% plot. The R2 values between measured and predicted total sediment yield and runoff were 0.83 and 0.33, respectively.